2019
DOI: 10.1002/ardp.201800309
|View full text |Cite
|
Sign up to set email alerts
|

Potent and highly selective dual‐targeting monoamine oxidase‐B inhibitors: Fluorinated chalcones of morpholine versus imidazole

Abstract: Two series of fluorinated chalcones containing morpholine and imidazole-based compounds (f1-f8) were synthesized and evaluated for recombinant human monoamine oxidase (MAO)-A and -B as well as acetylcholinesterase inhibitory activities.Our results indicate that morpholine containing chalcones are highly selective MAO-B inhibitors having reversibility properties. All the imidazole-based fluorinated chalcones showed weak MAO inhibitions in both isoforms. Among the tested compounds, (2E)-3-(3-fluorophenyl)-1- [4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 48 publications
(47 reference statements)
0
26
0
Order By: Relevance
“…Most recently, Mathew et al developed two series of fluorinated chalcones containing either morpholine or imidazole and found that the morpholine‐based compounds were potent and highly selective hMAO‐B inhibitors, whereas the imidazole analogs demonstrated weak hMAO‐A and ‐B inhibitory activity. The morpholine series also demonstrated moderate inhibitory activity on AChE (IC 50 ~ 24‐54 μM) and good BBB permeation.…”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 99%
“…Most recently, Mathew et al developed two series of fluorinated chalcones containing either morpholine or imidazole and found that the morpholine‐based compounds were potent and highly selective hMAO‐B inhibitors, whereas the imidazole analogs demonstrated weak hMAO‐A and ‐B inhibitory activity. The morpholine series also demonstrated moderate inhibitory activity on AChE (IC 50 ~ 24‐54 μM) and good BBB permeation.…”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 99%
“…Of those synthesized, compound 15 inhibited AChE and MAO‐B with IC 50 values of 4.91 and 0.29 µM, respectively, and at 25 µM reduced self‐induced Aβ 1–42 aggregation and Cu 2+ ‐induced Aβ 1–42 aggregation by 89.5% and 79.7%, respectively . Mathew et al synthesized two series of fluorinated chalcones containing morpholine or imidazole‐based compounds and evaluated them against recombinant hMAO‐A and ‐B and acetylcholinesterase. This study corroborated the MAO and AChE inhibitory effects of morpholine and imidazole heterocyclic nuclei located at the para position of ring A of fluorinated chalcones.…”
Section: Overview Of Dual‐acting Mao and Che Inhibitorsmentioning
confidence: 99%
“…[ 18 ] The FDA approved MAO‐B inhibitors selegiline and rasagiline are currently coadministered with levodopa for the relief of motor fluctuations in early‐stage PD, and selective, reversible type MAO‐B inhibitors safinamide and lazabemide are currently undergoing clinical trials. [ 19,20 ] Many privileged structural scaffolds like chalcones, chromones, coumarins and pyrazolines have been extensively explored as the basis of novel MAO‐B inhibitors, [ 21‐33 ] and thus, new classes of selective, reversible MAO‐B inhibitors are viewed with considerable interest in the contexts of AD and PD.…”
Section: Introductionmentioning
confidence: 99%